The Impact of Globalization and Modern Technology on the English Language - Rahmani, Habiburahman; Karimi, Mohammad Ilyas (International Journal of Language and Literary Studies, 2025)
English has changed significantly as a result of globalization and technology, and languages are constantly changing due to the demands of their users. As new words are created and become naturalized, language evolves very gradually. Today, English is a universal language, and communicating is a prerequisite for success in the global market. This article explores how globalization and technology have influenced the English language and its usage, emphasizing their various effects. This work has synthesized and analyzed the available literature using the systematic review technique, providing valuable insights into how technology and globalization have affected the English language. The results demonstrate how globalization has contributed to the widespread adoption of English as a lingua franca while also marginalizing regional languages. As English incorporates vocabulary from other cultures, linguistic borrowing has enhanced the language. On the other hand, technology has altered communication methods and has rapidly influenced the English language. Traditional communication methods have changed due to technology, which has made language more approachable and informal. Slang, abbreviations, emojis, and sentence fragments are new language forms brought about by the growth of texting, social media, and online communication. Although technology has facilitated faster and more effective communication, it has also caused a shift from standard grammar and language usage, particularly among younger generations.